Hypersurfaces of prescribed Gauß curvature in exterior domains - Finster, Felix; Schnürer, Oliver C. (My University, 2002)
We prove an existence theorem for convex hypersurfaces of prescribed Gauss curvature in the complement of a compact set in Euclidean space which are close to a cone.
Keywords: 510; 35J65; 53C42; 35J25; 53C21